Exploring Class Struggles in Marine Conservation: The Live Reef Fish Trade in Natuna and the Anambas Islands Indonesia - Arieta, Siti (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
This study discusses the important context related to class struggle in the context of Live Reef Fish Food Trade (LRFFT) in Natuna Regency and Anambas Islands. This area, known as a supplier of live reef fish, faces a dilemma between marine conservation policies and local economic sustainability. With the global backdrop of marine conservation targets, such as the '30 × 30' set by UNEP-WCMC in 2021, it is important to understand the dynamics of class struggle in achieving these goals. Although marine conservation is considered a solution to overcome overfishing and reduce endangered species, resistance from local communities indicates the complexity of implementing conservation policies. This study aims to fill the gap in knowledge related to the dimensions of class struggle in the context of marine conservation, focusing on LRFFT in Natuna and Anambas. Through a sociological theoretical framework, this study seeks to understand the dialectical relationship between agents (local communities and fishermen groups) and structures (conservation policies) and their impacts on the success or failure of policies. By detailing the geographical context, existing conservation policies, and challenges faced by local communities, this study hopes to provide further insights to help design more inclusive and sustainable marine conservation policies in the future.